KONSEP DIRI ANAK JALANAN DI PUSAT PERBELANJAAN RAMAYANA KOTA PEKANBARU - Nirwana Herda Riana; Rosmawati Rosmawati; Donal Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the phenomenon of street children whohave developed a long time, street children are children who most of the time spent tomake a living or roam the streets or other public places, their ages range from 6 yearsto 18 years. This study aims to describe how the self-concept and characteristics ofstreet chiladren in Ramayana shopping center, Pekanbaru City. The subjects in thisstudy were 6 children. The method used in this research is qualitative with descriptiveresearch type to clearly describe the characteristics and self-concept of street children.Data collection techniques used are observation, structured interviews anddocumentation, there are 4 steps of data analysis in this study, namely data collection,data reduction, data presentation, drawing conclusions. From the results of the studyfound street children aged 9-12 years, still attending school and some others notattending school, living with parents and some others living with adoptive parents,doing these activities to help the family economy and increase pocket money, selfconceptstreet children in the Ramayana shopping center Pekanbaru City is high, from 4aspects (physical, social, moral, psychological) only 1 aspect is low, namely moralaspects.Key Word : Street Children, Self Concept